The Use of Contradictory Framing in International Conflicts : Frame Analysis of Statements Regarding the Israel-Palestine Conflict - Koivuporras, Tuisku (My University, 2024)
In this Bachelor’s thesis I examine how language is used to present conflict situations according to the speaker’s political interests and ideologies. I examine this through the Israel-Palestine conflict. My materials consist of two statements to the United Nations, one given by the Israeli UN representative Gilad Erdan and one by the Palestinian UN ambassador Riyad Mansour. As my theoretical framework I use frame analysis popularised by Erving Goffman in 1986. I developed six frames based on my analysis and examined the use of these frames in the statements. The analysis showed that even though the two speakers have contradictory views of the situation, they have the same objectives behind the statements. Both speakers use different frames to portray their side as the oppressed group and the other side as the oppressor. The analysis also showed that ethnicity and religion are important themes when discussing the conflict, as the two speakers highlighted them in their statements. Other themes that rose from the analysis are peace, international law, and terrorism. There are possibilities for further research of these themes in the study of language and conflicts.
Keywords: framing, conflicts, Israel-Palestine